Tomboys Revisited: A Retrospective Comparison of Childhood Behavioral Patterns in Lesbians and Transmen - Randi, Ettner; Frederic, Ettner; Loren, Schechter; Tanya, Friese; Tonya, White (Journal of Child and Adolescent Psychiatry, 2018)
In 1979, a study conducted by Ehrhardt et al. retrospectively examined childhood behavioral patterns of 30 adults; 15 identified as lesbian women and 15 identified as transmen. All 30 adults had been assigned female at birth, and, as children, all were regarded as “tomboys.” The study found several key factors that distinguished the two cohorts. The goal of this study was to replicate and extend the 1979 study, utilizing a larger sample size and including a reference group of heterosexual women. Given the major social, technological, medical, and legal paradigm shifts that have occurred over the past four decades, we sought to determine if the previous findings still differentiate the cohorts. In light of the exponential rise in the number of gender diverse and dysphoric youth who request treatment, providing optimal, affirmative care and education is paramount, especially since many of these young people seek social and/or medical transition. Exploration of the early behavioral indices of the diverse trajectories may help to inform best practices for optimal care for these young people and their families.
Keywords: gender; lesbian; transgender; transmen